Finnish risk score for detection of dysglycemia in adults in the Family Medicine Unit - García-Morales, Gabriela (2023)
Objective: to establish the discriminative capacity of the Finnish risk score for dysglycemia in users of a family medicine unit located in the suburbs of the State of Guerrero, Mexico. Material and methods: We conducted a cross-sectional study from March to December 2021 in a Family Medicine Unit. With prior informed consent, we applied the Finnish risk score for the detection of dysglycemia to 200 people between the ages of 20 and 60, we obtained somatometric measurements and fasting plasma glucose figures. We estimated sensitivity, specificity, positive and negative predictive value, positive and negative likelihood ratio, and calculated the area under the curve (AUC) to estimate the discriminative ability of the risk score, where the reference test was fasting glucose. We performed bivariate analysis to identify factors associated with dysglycemia, obtaining Odds Ratio (OR) and 95% confidence intervals (95%CI). Result: The occurrence of dysglycemia was 26.5% (53/200). The AUC of the ROC curve of the Finnish score for dysglycemia was 0.65 (95%CI 0.57-0.74). The factors associated with diabetes were ≥40 years (OR 2.1; 95%CI 1.1-3.9), body mass index ≥25 Kg/m2 (OR 2.8; 95%CI 1.2-6.7) and suffering from arterial hypertension (OR 2.2; 95%CI 1.1 -4.4). Conclusions: The FINDRISC was shown by AUC to be a poor tool for detecting people at risk of suffering from dysglycemia, in a population attached to a suburban medical unit